2018
DOI: 10.1021/acs.jpcb.8b01631
|View full text |Cite
|
Sign up to set email alerts
|

How Proton Transfer Equilibria Influence Ionic Liquid Properties: Molecular Simulations of Alkylammonium Acetates

Abstract: Protic ionic liquids (PILs) form through proton transfer from a Brønsted acid to a Brønsted base. In this work we use molecular dynamics simulation to study how PIL properties vary with χ, the extent of the proton transfer reaction. Three PILs are considered: N-propylammonium acetate, [N3][Ac], N-butylammonium acetate, [N4][Ac], and N, N-dimethylbutylammonium acetate, [N114][Ac]. In all cases density and viscosity increase with increasing χ, while diffusivities of all species decrease with increasing χ. In eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Spectroscopic approaches have been proposed to quantify the proton transfer [43], but the method proposed relies on the assumption that the solvation shells and dielectric constant of the systems stay unperturbed upon changing the composition of the system, which is questionable. MacFarlane's group extensively addressed the proton transfer topic [39,44,45], but always accounting for ΔpKa values, which are strictly meaningful only in aqueous systems. They also pointed to the proton transfer's qualitative spectroscopic determination [44], but again overlooking the different chemical environments experienced by the species in the Brønsted precursors and the ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic approaches have been proposed to quantify the proton transfer [43], but the method proposed relies on the assumption that the solvation shells and dielectric constant of the systems stay unperturbed upon changing the composition of the system, which is questionable. MacFarlane's group extensively addressed the proton transfer topic [39,44,45], but always accounting for ΔpKa values, which are strictly meaningful only in aqueous systems. They also pointed to the proton transfer's qualitative spectroscopic determination [44], but again overlooking the different chemical environments experienced by the species in the Brønsted precursors and the ILs.…”
Section: Introductionmentioning
confidence: 99%
“…121 That the self-solvation properties of the final liquid towards the ions is a crucial, albeit difficult to predict, ingredient to understand the extent of equilibrium in reaction (1) has clearly emerged in a series of recent works. [122][123][124][125] An example of how simple molecular indicators can be misleading in understanding ionicity in a given PILs is triethylammonium acetate (TEAAc). Judging from pKa, one expects to find a majority of acetates and ammonium cations.…”
Section: The Problem Of Ionicitymentioning
confidence: 99%
“…Recently, Gelb et al used molecular dynamics simulation to investigate how ionicity influences the properties of PILs. 50 They found that the viscosity increased with increasing ionicity, and the conductivity was affected by the concentration and the diffusion constant of the ions. 47 From those reported viscosities (5.6 × 10 −3 and 1 × 10 −3 PaÁs at 353 K) and conductivities (0.4 and 0.1 SÁm −1 at 300 K), 5,32 the PIL with higher ionicity also has higher conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Those authors observed that the thermal stability of PILs was almost linearly related to the aqueous ΔpKa values. Recently, Gelb et al used molecular dynamics simulation to investigate how ionicity influences the properties of PILs 50 . They found that the viscosity increased with increasing ionicity, and the conductivity was affected by the concentration and the diffusion constant of the ions.…”
Section: Introductionmentioning
confidence: 99%